2018
DOI: 10.3390/molecules23102576
|View full text |Cite
|
Sign up to set email alerts
|

Safe Synthesis of 4,7-Dibromo[1,2,5]thiadiazolo[3,4-d]pyridazine and Its SNAr Reactions

Abstract: A safe and efficient synthesis of 4,7-dibromo[1,2,5]thiadiazolo[3,4-d]pyridazine from the commercial diaminomaleonitrile is reported. Conditions for selective aromatic nucleophilic substitution of one or two bromine atoms by oxygen and nitrogen nucleophiles are found, whereas thiols formed the bis-derivatives only. Buchwald-Hartwig or Ullmann techniques are successful for incorporation of a weak nitrogen base, such as carbazole, into the [1,2,5]thiadiazolo[3,4-d]pyridazine core. The formation of rather stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…Mono-adducts 3a – c and 4 were synthesized by nucleophilic aromatic substitution with appropriate amines [34] and by Suzuki cross-coupling reaction with boronic acid, following the procedures described [33] (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mono-adducts 3a – c and 4 were synthesized by nucleophilic aromatic substitution with appropriate amines [34] and by Suzuki cross-coupling reaction with boronic acid, following the procedures described [33] (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…It was found that substitution chemistry of 4,7-dibromo[1,2,5]thiadiazolo[3,4- d ]pyridazine (aromatic nucleophilic and palladium-catalysed cross-couplings) was a powerful tool for the selective formation of various mono- and bis-derivatives of strong electron-accepting heterocycles. Conditions for selective aromatic substitution of one bromine atom by oxygen and nitrogen nucleophiles [34], as well as by Suzuki-Miyaura coupling by arylboronic acids, were found. These results have driven us to the conclusion that this might be a good basis for the synthesis of dyes for DSSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown that 4,7-dibromo [1,2,5]thiadiazolo [3,4-d]pyridazine 1 can be safely and efficiently prepared from the commercial diaminomaleonitrile [12]. Herein, we examined the reduction of this compound (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…During our investigation of the nucleophilic substitution in 4,7-dibromo [1,2,5]thiadiazolo[3,4-d]pyridazine 1 by alkoxide anions we observed the formation of the new compound as a side product which was proved by mass-spectrometry to be 3,6-dibromopyridazine-4,5-diamine 2. We showed that the treatment of 1 with sodium methoxide in MeOH led to the formation of bis(methoxy) derivative 3 [12] with a traces of diamine 2 (Entry 3). To develop the synthetic approach to the target compound 2 we investigated this reaction in other solvents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation